Integrating Venezuelan Migrants in Colombia’s Agri-Food Sector - Sebastian, Ashwini Rekha (World Bank, Washington, DC, 2020)
By the end of August 2020, five years since the intensification of the Venezuelan humanitarian crisis, 5.2 million Venezuelans had fled their country, in an exodus whose scale and pace closely mirror those of the Syrian refugee crisis - where by 2015, four years into the forced displacement crisis, 4.8 million people had escaped Syria. In the immediate aftermath of the surge in the number of Venezuelan migrants, the focus of the Colombian government was to register all migrants and provide relief through health and welfare systems. This report is intended to reach a broad audience of policy makers, program administrators, development professionals, and academics in Colombia and in the broader development community, and aims to assesses the integration of Venezuelan migrants into Colombian agri-food labor markets through a combination of original micro-level data analysis and in-depth semi-structured field interviews with Venezuelan migrants, producers’ associations, and Colombian institutions. The main contributions of the study are three-fold. First, the report offers a detailed overview of Venezuelan migration into Colombia, spatially and over time, enriching with new, and more detailed, insights the currently available information on migrants’ employment outcomes and on their comparison to those of the local Colombian population. A second contribution of the report is to provide evidence that the agri-food sector in Colombia has a yet unfulfilled potential to support a smoother inclusion of Venezuelan migrants in the labor force. The third and final contribution of the report is to identify lessons learned for the inclusion of Venezuelan migrants in the agri-food sector in Colombia. The report concludes with a look at the path ahead, through practical ideas and operationalization principles for delivering a strategy that includes both supply and demand driven integration of migrants in labor markets, featuring agriculture and food systems more prominently.